Sosialisasi Produk Pangan Sehat Berbasis Olahan Jagung Manis Bagi Kader PKK Desa Sentul Kecamatan Tembelang Kabupaten Jombang - Mochammad Chumaidi; Miftachul Chusnah; M Isa Hilalurochmafa; Anggi Indah Yuliana; Siti Nur Qomariyah; M Ainul Yaqin; Kustia Eka Pratama (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Provision of nutritious food sources is one of the priorities in maintaining public health. Therefore, community service activities aimed to: (1) providing understanding to the community, especially PKK cadres, the importance of maintaining a healthy lifestyle by regulating the composition of food/drinks and food diversification and (2) providing knowledge for PKK cadres on how to make healthy food products made from corn. This community service activity was carried out in October - November 2021 with the target of PKK cadres in Sentul Village, Tembelang District, Jombang Regency. This activity was carried out using the ABCD (Asset Based Community Development) approach, which utilizes village assets in the form of sweet corn as a healthy food product. The implementation of community service activities consisted of two stages, including observation and coordination with the Sentul Village PKK management and socialization of healthy food products in the form of juice and sweet corn ice cream. The results of the socialization of healthy food products based on processed sweet corn have an impact was (1) providing understanding to PKK cadres about healthy food diversification innovations based on local ingredients, and (2) providing knowledge to PKK cadres on how to make easy processed products in the form of juice. and sweet corn ice cream.